Informative value of online monitoring of turbo generator technical condition parameters compared to visual inspection - I. V. Yaroshenko; V. V. Nosenko; M. S. Altunina; Yu. P. Aksenov (Омский научный вестник)
Measurements of partial discharge amplitudes and spectral analysis of vibration at different times and often by different people are poorly informative, which are accepted in the practice of turbine generator diagnostics. The information content is much higher when both discharges and vibrations are measured at the same point, this allows you to see both the synergy of “vibration phenomena and discharges” and the reverse synergy of “discharges and vibration phenomena”. And the analysis of the distribution of the magnetic field over the surface of the generator housing makes it possible to identify the result of the “operation” of the discharges and vibration. To determine their effect on tires and current-carrying elements of turbo generators the paper provides practical examples of determining defect zones using this method and confirming them during visual and instrumental inspection during repairs.